Consumers’ Intention to Switch from Green and Conventional Cosmetics - Asri Sekar Mawar Firdausi; Resita Septia Rahma; Lita Ningrum Afriani (Universitas Prasetiya Mulya, 2023)
Consumers play an essential role in consuming activities since it can impact environmental preservation. However, previous research stated that the ineffectiveness of green products resulted in consumers choosing to use conventional products. Hence, this study aims to determine the factors that cause consumers to switch from green products to conventional products in cosmetics. The theory applied in explaining the phenomenon is migration theory by using the push-pull-mooring framework. The subjects of this study were 205 green cosmetics consumers who collected the data using questionnaires. Based on the results of data analysis, the pull factor and push factor are the most decisive factors that influence the consumers switching intention to conventional cosmetics. Meanwhile, the mooring factor does not moderate the push and pull factors on the customers’ switching intentions to conventional cosmetics.